Genome Sequence of Paracoccus sp. JM45, a Bacterial Strain Isolated from a Marine Sponge with a Dual Quorum Sensing Inhibition Activity. - Gutiérrez Barranquero, Jose A.; López Parages, María; Dobson, Alan; Reen, F. Jerry; O´Gara, Fergal (American Society for Microbiology (ASM), 2019)
The draft genome sequence of Paracoccus sp. strain JM45, isolated from a marine sponge harvested off the west coast of Ireland, is reported here. Quorum sensing and quorum sensing inhibition activities have been reported recently for this bacterium, and genomic analysis supports its potential use for novel therapeutic development.
Keywords: Bacterias gram negativas - Aspectos moleculares; Paracoccus sp. JM45; Genome sequence; Marine sponges; Quorum sensing